THE PHILOSOPHY OF ALL OF US: THE MEANING OF LIFE ACCORDING TO AYN RAND - Kasprike, Milton Leonardo Espíndola (Seven Editora, 2024)
Ayn Rand states that everyone has a philosophy called the sense of life that acts as an automatic evaluator of all thoughts, emotions and actions of individuals. The objective of the article is to present this concept, demonstrate its practical application and expose what are the philosophical issues involved. Methodologically, the article performs a theoretical analysis of the works of Rand and her main collaborators. The article explores how the sense of life is formed subconsciously and how it influences the subject's perception of reality and self-esteem. Knowing about the meaning of life is fundamental to all men, as ignorance can lead to an existence guided by unexamined and contradictory ideas, which leads to negative emotions and the passivity of actions. The conscious confrontation of the philosophical questions that Rand presents is the process that all men must go through in order to achieve a more harmonious, self-confident, and fulfilled life. Finally, the article emphasizes that it is only through philosophy that man can develop a benevolent sense of life, which recognizes reason as an absolute, reality as knowable, the human being as good, and happiness as a goal. DOI:https://doi.org/10.56238/sevened2024.029-006